Does aerobic exercise training alter responses to opioid analgesics in individuals with chronic low back pain? A randomized controlled trial. Issue 8 (August 2021) - Bruehl, Stephen; Burns, John W.; Koltyn, Kelli; Gupta, Rajnish; Buvanendran, Asokumar; Edwards, David; Chont, Melissa; Wu, Yung Hsuan; Stone, Amanda
Abstract : Abstract: We tested whether aerobic exercise training altered morphine analgesic responses or reduced morphine dosages necessary for adequate analgesia. Patients with chronic back pain were randomized to an 18-session aerobic exercise intervention (n = 38) or usual activity control (n = 45). Before and after the intervention, participants underwent 3 laboratory sessions (double-blinded, crossover) to assess effects of saline placebo, i.v. morphine (0.09 mg/kg), and i.v. naloxone (12 mg) on low back pain and evoked heat pain responses. Differences in evoked and back pain measures between the placebo and morphine conditions indexed morphine analgesia, with pre-post intervention changes the primary outcome. Endogenous opioid analgesia was indexed by differences in evoked and low back pain measures between the naloxone and placebo conditions. A Sex X Intervention interaction on the analgesic effects of morphine on visual analogue scale back pain intensity was observed ( P = 0.046), with a similar trend for evoked pain threshold ( P = 0.093). Male exercisers showed reduced morphine analgesia pre-post intervention, whereas male controls showed increased analgesia (with no differences in females). Of clinical significance were findings that relative to the control group, aerobic exercise produced analgesia more similar to that observed after receiving ≈7 mg morphine preintervention ( P < 0.045). Greater pre-post intervention increases in endogenous opioid function (from any source) were significantly associated with larger pre-post intervention decreases in morphine analgesia ( P < 0.046). The overall pattern of findings suggests that regular aerobic exercise has limited direct effects on morphine responsiveness, reducing morphine analgesia in males only. Abstract : Supplemental Digital Content is Available in the Text.An aerobic exercise intervention reduced morphine efficacy in patients with chronic back pain, but also produced analgesia comparable to that observed after ≈7 mg morphine administered preintervention.